[Christmas special [videorecording] - Lazaro, Cheche; Ramos, Angie; Santos, Owen (The Probe Team, 1992)
Probe embarks on a collaborative Christmas special with 5 and up, featuring the traditions that make for a truly Filipino Christmas.